The Mediating Role of Trust in the Relationship Between Familiarity and Repurchase Intention of Consumers in Nunukan Regency - Karunia, Erick; Azis, Muh. Irfandy; Muthalib, Dzulfikri Azis; Loong, Ang Hong; Mojolou, Dean Nelson (INOVASI: Jurnal Ekonomi, Keuangan, dan Manajemen, 2024)
This study aims to examine the influence of familiarity on consumers repurchase intentions, along with the role of trust as a mediating variable in this relationship. Using Structural Equation Modeling (SEM), this study analyzes data from 255 respondents who are online shop users in Nunukan Regency to test hypotheses regarding inter-variable relationships. The analysis results indicate that familiarity has a positive and significant effect on consumer trust (p = 0.001) and directly increases repurchase intention (p = 0.000). Additionally, trust is proven to mediate the relationship between familiarity and repurchase intention, with a significant total effect (p = 0.001). These findings suggest that higher levels of consumer familiarity with online shopping lead to stronger trust, ultimately enhancing consumers' repurchase intentions. This study contributes to understanding the psychological factors influencing consumer loyalty and provides practical implications for marketing strategies aimed at increasing customer loyalty through improved familiarity and trust